(untitled) (The Peerian Journal, 2024)
The goal of the research is to identify The effect of teaching history using the Barman model on developing lateral thinking among fifth grade literary students In order to achieve the research goal, the researcher tested the null hypothesis that was expected There are no statistically significant differences between the average achievement scores of the experimental group students who study history using the Barman model and the average achievement scores of the control group who study the same subject without using the Barman model. The research community consisted of fifth-grade literary students in secondary and middle schools affiliated with the First Karkh Baghdad Education Directorate, who numbered (1544) students. While the random research sample consisted of (54) students, with (27) students in the experimental group, and (27) students in the control group, the researcher relied on the statistical analysis program